1996
DOI: 10.1038/380595a0
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a mammalian phosphoinositide-specific phospholipase Cδ

Abstract: Mammalian phosphoinositide-specific phospholipase C enzymes (PI-PLC) act as signal transducers that generate two second messengers, inositol-1,4,5-trisphosphate and diacylglycerol. The 2.4-A structure of phospholipase C delta 1 reveals a multidomain protein incorporating modules shared by many signalling proteins. The structure suggests a mechanism for membrane attachment and Ca2+-dependent hydrolysis of second-messenger precursors. The regulation and reversible membrane association of PI-PLC may serve as a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
573
0
10

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 565 publications
(614 citation statements)
references
References 42 publications
31
573
0
10
Order By: Relevance
“…These linkers are not or only partially resolved in the crystal structures [5,6] and are susceptible to proteolysis [23] suggesting high flexibility. The number of charged amino acids, especially the long stretch of negatively charged residues, in PLC-β2 is striking.…”
Section: Catalytic Domain and Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…These linkers are not or only partially resolved in the crystal structures [5,6] and are susceptible to proteolysis [23] suggesting high flexibility. The number of charged amino acids, especially the long stretch of negatively charged residues, in PLC-β2 is striking.…”
Section: Catalytic Domain and Mechanismmentioning
confidence: 99%
“…As detailed below, some protein regulators change the level of Ca 2+ required for PLC-δ activation. PLC-δ1 was the first mammalian PLCs to have high resolution structures available [5,6] and, since it can be expressed easily, a great deal of biophysical information is available (see [7]) allowing us to contrast its properties with other, closely related PLCs.…”
Section: Introductionmentioning
confidence: 99%
“…While the biological role of bacterial PI-PLCs is not clear, it has been shown that these enzymes may contribute to virulence of the respective microorganisms (14,15). Since both eukaryotic and bacterial enzymes appear to catalyze the same chemical reactions (12,(16)(17)(18)(19), bacterial PI-PLCs have been a favorite model system in mechanistic and structural studies because of their low molecular weight and absence of regulatory domains (20)(21)(22)(23)(24)(25). However, there are significant differences between these two types of enzymes: bacterial enzymes accept only nonphosphorylated phosphatidylinositol (PI) substrates and produce mainly cyclic inositol phosphate (IcP), which is subsequently hydrolyzed at a rate that is 1000-fold slower; in contrast, mammalian enzymes prefer phosphorylated PI substrates and produce IcP and inositol phosphates (IP) simultaneously.…”
mentioning
confidence: 99%
“…Interestingly, the novel C2 domain factor has only 7 β strands (Fig. 2) in comparison with 8 stranded β-sandwich in other C2 domains of C2-domain superfamily proteins, such as PLC-δ, SynC2A, cPLA2, PKC-δ and PKC-β (Sutton et al, 1995;Essen et al, 1996;Perisic et al, 1998;Sutton and Sprang, 1998;Pappa et al, 1998). Also, the four putative proteins in zebrafish (GenBank accession no.…”
Section: Screening Cloning and Characterization Of A Novel C2 Domainmentioning
confidence: 99%
“…CAI11880), and the novel C2 domain factor (EcOC2) identified from orange-spotted grouper in this study. The secondary structure of C2 domain from PLC-δ was determined by X-ray (Essen et al, 1996;Jiménez et al, 2003). The 8 β-strands in PLC-δ C2 domain are shown in blank arrows.…”
Section: Ovary-specific Expression Of C2 Domain Factor During Artificmentioning
confidence: 99%